Enhancing English Speaking Proficiency through Mobile-Assisted Language Learning with the Cake Application among University Students - Ikha’a, Anadza Awaenal (BATARA DIDI : English Language Journal, 2023)
This research aims at assessing the impact of Cake application developed and used as a MALL platform in increasing the university students’ abilities to speak English fluently. In this study, the quasi-experimental design was adopted and the participants were 100 in number and divided into two groups; the experimental group that used Cake application and the control group that followed the traditional curriculum without the application. The Speaking Proficiency Assessment Framework (SPAF) was used to pre-test and post-test Speaking skills with focus on pronunciation, fluency, lexical resource, and communicative competence. The scores highlighted significant enhancement of the level of speaking in the experimental group, the size of which substantiated as rather large, proving the efficacy of the given intervention in the context of its practical application. The distribution analysis revealed that the scores are distributed less variable in the posttest of the experimental group than in the pretest, which suggests the likelihood that the Cake application was beneficial in augmenting performance while assisting students with lower and higher initial proficiency levels. Such perspectives point towards the ability of the MALL tools in the delivery of education especially to those in need.